Evaluación de la afectación del Río Bogotá causada por el vertimiento generado en un proceso de curtido de pieles, tramo Villapinzón – Río Tejar (2018)
The evaluation of the effects of the Bogotá River caused by the dumping generated in a leather tanning process in the section between the Villapinzón and Río Tejar upstream stations, was carried out taking into account the impact of 15 variables associated with the physicochemical quality of water (electrical conductivity, total chromium, BOD, COD, organic phosphorus, inorganic phosphorus, organic nitrogen, nitrates, ammonium ions, dissolved oxygen, pH, total suspended solids , alkalinity, sulfides and temperature). Likewise, by the Pugh's matrix selection, it was determined that the QUAL2K model is the free software that best approximates the conditions and behavior of the Bogotá river to the reality of the system, predicting the way in which the point source discharge of the discharge disturbs the water body. This disturbance becomes noticeable when comparing the results of the water quality analysis for total phosphorus, nitrates, total suspended solids and sulfides with the maximum permissible limits established in Resolución 0631 de 2015 and those of BOD with the maximum permissible limits established in Acuerdo 043 de 2006, obtaining as a result that they are exceeded by 94, 474, 26, 29 and 200 percent respectively; allowing to conclude that the discharge coming from the productive process of the transformation of animal skin into leather in the municipality of Villapinzón, still does not fulfill with the minimum requirements established by the environmental regulation entities that govern the Colombian territory, so that the Bogotá River does not is affected by its dumping.